Penerapan Model Pembelajaran Improve Pada Materi Nahwu Dalam Meningkatkan Maharoh Qiro’ah Santri PP Darul Lughah Wal Karomah - Wijaya, Mualim (CV. Satria Jaya, 2023)
Learning in class is often considered a boring and boring experience by students or students. The learning model that is generally used by teachers is the classical and monotonous model, and this often results in difficulties for students in understanding the material presented. This study aims to explain the application of the